Problems, possibilities, promising practices: Critical dialogues on the Olympic and Paralympic Games (Eleventh International Symposium for Olympic Research, 2012)
P. R. Sailors: "Organically Sound" Olympians: Gender and Women's Distance Running F. Mason: Choices of Commemoration: Analysis of Canadian Winter Olympic Commemorative Videos T. Rider: 'It Is Not a Simple Matter to Keep Aloof': Avery Brundage and the U.SGovernment in the Early Cold War Years M. S. Doiara S. dos Santos: Growing Pains: Avery Brundage and the Olympic Movement in South America M. P. Llewellyn & J. T. Gleaves: The Rise of the 'Shamateur': The International Olympic Committee and the Preservation of the Amateur Ideal S. Teetzel: Olympic Support Personnel and Entourages: Coherence with the Philosophy of Olympism N. Masumoto: Yo u t h O l y m p i c G a m e s : A New Paradigm in the Quest for Transnationalism J. Krieger: The Youth Olympic Games from the Athlete's Perspective L. R. Gerlach: An Olympic Friendship: Alma Richards and Hans Liesche M. Devitt: Olympic Education: Gold Medal for Propaganda? J. R. Pate & R. Hardin: The Model for US Paralympic Training Sites: A Case Study of the Lakeshore Foundation S. Wassong & J. Krieger: Munich 1972-Turning Point in the Olympic Doping Control System: The First Official Appearance of Doping Concerns on the Agenda of the International Olympic Committee T. Batuhan: The Politics of Olympic Transportation Planning: The Case of the 1996 Atlanta Summer Olympic Games K. Homma & Naofumi Masumoto: How Social Factors Developed Sport Legacies after the Sydney 2000 Olympic Games I. Ritchie: The 'Spirit of Sport': Understanding the Cultural Foundations of Olympism through Anti-Doping Policies K. Henne: Tracing Olympic Bio-Citizenship: The Implications of Testing for Ineligibility C. Weaving: 'Babes Boxing in Skirts:' A Critique of the Proposed AIBA Uniform Rule A. Schweinbenz: 'Float Like a Butterfly, Sting Like a Bee'-But Only if You Dress Like a Girl: An Analysis of the Feminization of Female Olympic Athletes through Athletic Attire C. O'Bonsawin: Igniting a Resistance Movement: Understanding Indigenous Opposition to the 2010 Olympic Torch Relay W. E. Wakefield: Citius, Altius, Fortius: At Whose Expense? Making Sense of the Death of Nodar Kumaratishvili at the 2010 Olympic Winter Games G. Nichols & R. Ralston: Volunteer Management at the 2012 Olympic Games: A Tension between 'Programme' and "Membership' Management Styles R. Baka: Olympic Houses: A Comparative Investigation Between Canada, Germany and Australia